(untitled) (Research, Society and Development, 2021)
The Food and Nutrition Units (UANs) are responsible for the production of meals, whose objective is to meet the nutritional demands of individuals. Within these units, there has been an increase in the number of foodborne diseases (DTAs), requiring greater care in food handling at these sites. In this context, employees working in this field become potential tools in the transmission of these diseases through their own food. Due to this problem, ANVISA issued RDC nº 216/04 that recommends periodic training in Good Manufacturing Practices. Therefore, this study aimed to evaluate the impact of a GMP course for food handlers in schools and day care centers. The course was held in the municipality of Picuí-PB, and all food handlers of the municipal public network were considered. Questionnaires of sociodemographic and BPH profiles with a special focus on hygiene were applied in two moments, one before and one after the course. After completing the course, it was verified that 88.33% were female, 43.33% were over 40 years old, 56.66% had completed high school, 51.66% had a maximum of 5 years of work in function, it was also noted that only 14.99% went through a course in BPF or training in the space of one year since they were hired. After the course, it was verified that of the 20 questions corresponding to the GMP, in 15 of them there was an increase of correct answers, thus corroborating the importance of the qualification for food manipulators based on the current legislation and the potential positive effects.